2008
DOI: 10.1210/jc.2007-2308
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D2 Is as Effective as Vitamin D3 in Maintaining Circulating Concentrations of 25-Hydroxyvitamin D

Abstract: A 1000 IU dose of vitamin D2 daily was as effective as 1000 IU vitamin D3 in maintaining serum 25-hydroxyvitamin D levels and did not negatively influence serum 25-hydroxyvitamin D3 levels. Therefore, vitamin D2 is equally as effective as vitamin D3 in maintaining 25-hydroxyvitamin D status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
454
3
15

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(501 citation statements)
references
References 17 publications
21
454
3
15
Order By: Relevance
“…In our study, we found that sunbathing abroad or in Sweden during the summer had little or no effect on the risk, whereas sun bed users had a significantly reduced risk. The major source of vitamin D is sunlight, which penetrates the skin and converts 7-dehydrocholesterol to 25-hydroxicholecalciferol vitamin D 3 (25-OHVitD) through pre-vitamin D (Holick et al, 2008). Sweden is a Nordic country with a scarcity of sunlight during the winter and therefore many women will develop seasonal vitamin Ddeficiency, with low levels during winter.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that sunbathing abroad or in Sweden during the summer had little or no effect on the risk, whereas sun bed users had a significantly reduced risk. The major source of vitamin D is sunlight, which penetrates the skin and converts 7-dehydrocholesterol to 25-hydroxicholecalciferol vitamin D 3 (25-OHVitD) through pre-vitamin D (Holick et al, 2008). Sweden is a Nordic country with a scarcity of sunlight during the winter and therefore many women will develop seasonal vitamin Ddeficiency, with low levels during winter.…”
Section: Discussionmentioning
confidence: 99%
“…Ergocalciferol is produced by UV irradiation of the fungal steroid ergosterol and is used in some vitamin D supplements. Although the relative ability of vitamin D 2 to increase vitamin D status (as indicated by serum concentrations of 25-hydroxyvitamin D (s25(OH)D)) compared with vitamin D 3 was previously disputed, recent data from Holick et al (13) showed that vitamin D 2 was as effective as vitamin D 3 .…”
Section: Vitamin D Endocrine Systemmentioning
confidence: 99%
“…The available studies applied various VitD repletion approaches (relating to dose, duration, and route of administration and monitoring of 25(OH)D) and targeted dissimilar ranges of serum 25(OH)D levels. The two forms of nutritional VitD (D 2 , D 3 ) were regarded as equal and interchangeable [50], while recent literature suggests that VitD 3 (cholecalciferol) is more potent than VitD 2 (ergocalciferol) at lowering PTH levels [51][52][53]. Considering the advantages of various VitD analogs, such as low cost, minor risks for hypercalcemia and hyperphosphatemia, and survival benefit on HD population [54], it will be of interest to explore their usefulness, especially to determine whether concurrent use of 25(OH)D with 1,25(OH) 2 D or calcimimetics will provide better outcomes.…”
Section: Unresolved Controversies Surrounding 25(oh)d Administration mentioning
confidence: 99%